The Tale of the Three Brothers – Shh, Wnt, and Fgf during Development of the Thalamus - Hagemann, Anja I.; Scholpp, Steffen (Frontiers in Neuroscience, 2012)
The thalamic complex is an essential part of the brain that requires a combination of specialized activities to attain its final complexity. In the following review we will describe the induction process of the mid-diencephalic organizer (MDO) where three different signaling pathways merge: Wnt, Shh and Fgf. Here, we dissect the function of each signaling pathway in the thalamus in chronological order of their appearance. First we describe the Wnt mediated induction of the MDO and compartition of the caudal forebrain, then the Shh mediated determination of proneural gene expression before discussing recent progress in characterizing Fgf function during thalamus development. Then, we focus on transcription factors, which are regulated by these pathways and which play a pivotal role in neurogenesis in the thalamus. The three signaling pathways act together in a strictly regulated chronology to orchestrate the development of the entire thalamus.